Sistem Informasi Manajemen Hubungan Pelanggan Pada PT Ayek Selangis Corp Palembang - Lais, Nathacia; Mulyati, Mulyati (Universitas Multi Data Palembang, 2024)
In business there’ve been changes in the sales system. This change allows for great convenience and accessibility for people to start a business easily with little capital. In doing business, companies can utilize a customer relationship management information system. This system can automate sales, promotions and service. At PT Ayek Selangis Corp there’re problems with the follow-up process and billing to customers. From this problem, a solution is provided to develop customer relationship management information system. Purpose of using this customer relations information system is to make it easier for companies manage customer transactions, data, accommodate customer criticism and suggestions. Management information system was built using the Rational Unified Process (RUP) development method. System built will produce product sales system using the web. Then it has an email messaging feature to help companies send bills, promotions and other information to customers. There’s a reward feature helps companies increase customer loyalty.